2005
DOI: 10.1111/j.1462-5822.2005.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

The Francisella tularensis pathogenicity island protein IglC and its regulator MglA are essential for modulating phagosome biogenesis and subsequent bacterial escape into the cytoplasm

Abstract: SummaryThe Francisella tularensis subsp. novicida -containing phagosome (FCP) matures into a late endosome-like stage that acquires the late endosomal marker LAMP-2 but does not fuse to lysosomes, for the first few hours after bacterial entry. This modulation in phagosome biogenesis is followed by disruption of the phagosome and bacterial escape into the cytoplasm where they replicate. Here we examined the role of the Francisella pathogenicity island (FPI) protein IglC and its regulator MglA in the intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
328
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(343 citation statements)
references
References 38 publications
14
328
0
1
Order By: Relevance
“…Each of these portals of entry is a unique immunological niche so F. tularensis needs multiple ways to evade and/or modulate the immunological response. To date, the best-characterized F. tularensis immune evasion is its ability to invade host macrophages and escape the phagolysosomal degradation pathway (53)(54)(55). In this study, we identified a mechanism used by F. tularensis to alter both innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these portals of entry is a unique immunological niche so F. tularensis needs multiple ways to evade and/or modulate the immunological response. To date, the best-characterized F. tularensis immune evasion is its ability to invade host macrophages and escape the phagolysosomal degradation pathway (53)(54)(55). In this study, we identified a mechanism used by F. tularensis to alter both innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to microbial tolerance, there are other potential bacterial components and mechanisms that may contribute to the suppression of human DC activity. F. tularensis encodes a pathogenicity island (FPI) that is critical for survival and replication of the bacterium (36,37,43). Specifically, several of these genes have been shown to be important for F. tularensis escape from the phagosome, enabling replication of the bacterium in host cell cytoplasm (43).…”
Section: Discussionmentioning
confidence: 99%
“…F. tularensis encodes a pathogenicity island (FPI) that is critical for survival and replication of the bacterium (36,37,43). Specifically, several of these genes have been shown to be important for F. tularensis escape from the phagosome, enabling replication of the bacterium in host cell cytoplasm (43). Interestingly, one gene and the resulting protein have been implicated in both phagosomal escape (resulting in replication of the bacterium) and induction of tolerance in murine and human macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many intracellular bacteria depend on type III or type IV secretion systems in order to invade and survive within eukaryotic host cells but no such systems exist in F. tularensis, and the mechanisms behind its intracellular survival are not well understood (Larsson et al, 2005;Sjöstedt, 2006). After uptake into the host cell, the Francisella-containing phagosome evades fusion with the lysosome and bacteria rather quickly escape into the cytoplasm (Checroun et al, 2006;Clemens et al, 2004;Golovliov et al, 2003b;Santic et al, 2005). Several genes necessary for intramacrophage survival, growth within the amoeba Acanthamoeba castellanii, a putative natural reservoir of F. tularensis, and the phagosomal escape have been identified and most of them belong to the so-called Francisella pathogenicity island (FPI), which is a 34 kb genomic island (Lauriano et al, 2004;Nano & Schmerk, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, F. tularensis, like several other highly successful pathogens, possesses mechanisms to create an intracellular environment that favours its replication through subversion of the otherwise highly effective microbicidal response of phagocytic cells, and may serve as a prototype for stealth pathogens (Sjöstedt, 2006). Besides the evasion of phagolysosomal fusion, escape into the cytosol (Checroun et al, 2006;Clemens et al, 2004;Golovliov et al, 2003b;Santic et al, 2005), suppression of the inflammatory response upon escape into the cytosol (Rajaram et al, 2006;Telepnev et al, 2005) and abrogation of T-cell responses (Woolard et al, 2007), studies have identified additional intricate subversive mechanisms, such as inhibition of the IFN-c-induced STAT1 and iNOS expression in human and murine monocytic cells (Parsa et al, 2008;Roth et al, 2009). The concomitant reduced nitric oxide (NO) production could be directly linked to increased bacterial survival (Parsa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%